Understanding local food systems in South Asia: An assessment approach and design - Gupta, Manavi; Kishore, Avinash; Scott, Samuel P.; Chakraborty, Shreya; Chellattan, Prakashan Veettil; Choudhury, Samira; Krupnik, Timothy J.; Kumar, Neha; Neupane, Sumanta; Patwardhan, Sharvari; Sununtnasuk, Celeste; Urfels, Anton; et al. (International Food Policy Research Institute, 2022)
Home to one-quarter of humanity—one-fifth of whom are youth—South Asia has the world’s largest concentration of poverty and malnutrition (1–3). Despite producing one-quarter of the world’s consumed food, the region’s agrifood systems face formidable challenges in producing an adequate and affordable supply of the diverse foods needed for sustainable healthy diets (4,5). Unhealthy food consumption is rising, and farming systems are threatened by unsustainable groundwater withdrawal due to poorly developed food and energy policies. In addition, South Asia’s farmers are both contributors and victims of climate change and extreme weather, which contributes to rural out-migration—particularly of youth—resulting in rising labor scarcity and increased production costs. TAFSSA (Transforming Agrifood Systems in South Asia), a CGIAR Regional Integrated Initiative, aims to address these challenges by delivering actionable evidence and scalable innovations across these regions through a coordinated program of research and engagement from farmer to consumer. One of the roadblocks to addressing these challenges is the lack of credible and high-resolution data on food systems in the region. The TAFSSA food systems assessment aims to provide a reliable, accessible and integrated evidence base that links farm production, market access, dietary patterns, climate risk responses, and natural resource management in Bangladesh, India, Nepal and Pakistan. It is intended to be a multi-year assessment.